A Characterization of E-Benson Proper Efficiency via Nonlinear Scalarization in Vector Optimization. (28th April 2014) - Zhao, Ke Quan; Xia, Yuan Mei; Guo, Hui
Abstract : A class of vector optimization problems is considered and a characterization of E -Benson proper efficiency is obtained by using a nonlinear scalarization function proposed by Göpfert et al. Some examples are given to illustrate the main results.